2024
DOI: 10.3390/ani14111550
|View full text |Cite
|
Sign up to set email alerts
|

Love Hug—Functional Validation of Nuptial Pad-Secreted Pheromone in Anurans

Puyang Zheng,
Yuzhou Gong,
Bin Wang
et al.

Abstract: Chemical communication is an important mode of communication in the courtship and breeding processes of amphibians. In caudates, multiple components of sexual pheromones have been identified and functionally verified. One of these pheromone systems is plethodontid modulating factor (PMF). In anurans, the pheromone called amplexin was found in nuptial pads of ranids and was considered a member of the PMF system, yet its bio-function has not been tested. In this study, we obtained 18 amplexin transcript sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…For instance, in the treefrogs, Boana cinerascens (Spix, 1824) and Hyloscirtus phyllognathus (Melin, 1941), an association between the location of the male macroglands, high expression of the putative pheromone SPF and courtship behaviour has been suggested (Bossuyt et al, 2019). Furthermore, a recent study of the Yunnan pond frog (Nidirana pleuraden), found that proteins homologous to amplexins and plethodontid modulating factor, produced in the male's nuptial pads and transmitted to the female during amplexus, reduce courtship duration (Zheng et al, 2024). Across frogs, there is a diversity of amplexus types, including inguinal, axillary, cephalic, gular, glued, dorsal straddle, head straddle and loose axillary amplexus (Carvajal-Castro et al, 2020;Duellman & Trueb, 1994;Pough et al, 2016;Wells, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the treefrogs, Boana cinerascens (Spix, 1824) and Hyloscirtus phyllognathus (Melin, 1941), an association between the location of the male macroglands, high expression of the putative pheromone SPF and courtship behaviour has been suggested (Bossuyt et al, 2019). Furthermore, a recent study of the Yunnan pond frog (Nidirana pleuraden), found that proteins homologous to amplexins and plethodontid modulating factor, produced in the male's nuptial pads and transmitted to the female during amplexus, reduce courtship duration (Zheng et al, 2024). Across frogs, there is a diversity of amplexus types, including inguinal, axillary, cephalic, gular, glued, dorsal straddle, head straddle and loose axillary amplexus (Carvajal-Castro et al, 2020;Duellman & Trueb, 1994;Pough et al, 2016;Wells, 2007).…”
Section: Introductionmentioning
confidence: 99%